Akcja Wyborcza Polaków na Litwie w wyborach na Litwie - Gediminas Kazėnas (Politeja, 2014)
Electoral Action of Poles in Lithuania in elections in Lithuania. How Electoral Action of Poles in Lithuania managed to surpass the 5 percent electoral treshold?